Relational Resistance: (Re)telling and (Re)living Our Stories as Canadian Muslim Mothers and Daughters - Saleh, Muna (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
Drawing upon my experiences as a Canadian Muslim woman and mother, I engaged in a two-year narrative inquiry (Clandinin; Clandinin and Connelly) alongside three Canadian Muslim girls, and their mothers, as the girl co-inquirers transitioned into adolescence. Reverberating across the stories co-inquirers and I shared are experiences of living in the midst of, and in relation to, multiple arrogant perceptions (Lugones) and single stories (Adichie) of who we are— or should be—as good Muslim mothers and daughters. However, sharing, living, and inquiring into these stories alongside one another foregrounded the many ways we lived stories of relational resistance (Saleh, Stories We Live and Grow By). Ben Okri asserts that "one way or another we are living the stories planted in us early or along the way, or we are also living the stories we planted—knowingly or unknowingly—in ourselves" (46). Re-presenting my inquiry journey alongside one pair of mother (Layla) and daughter (Maya) co-inquirers, I make visible many of the stories we live by, with, and in (Clandinin; (Saleh, Stories We Live and Grow By).) and how, together, we inquired into many of the stories that have been planted in us, the stories we are planting in ourselves and others, and the stories that we are relationally shaping and reshaping alongside one another. Thinking alongside Hilde Lindemann Nelson’s (1995) conceptualization of chosen communities as sites of resistance to taken-for-granted, dominant narratives, I make visible how we resisted arrogant perceptions and single stories of us as Muslim mothers and daughters.